The relationship between home modifications and frailty among older adults: a scoping review protocol - Julius Ernst; Elisabeth Zwinge; Maximilian König (PLoS ONE, 2025)
Introduction The rapid aging of populations worldwide presents significant challenges to healthcare and social systems. Frailty—a multidimensional geriatric syndrome marked by physical weakness, exhausted reserve capacities across all organ systems, and increased susceptibility to adverse events—is prevalent among older adults. Ensuring an optimal fit between individuals and their living environment is vital for preserving independence and reducing the burden on both professional healthcare services and informal care. A supportive home environment may help delay the onset or progression of frailty, while a person-environment misfit is likely to accelerate physical decline. Home modifications may play a critical role in this regard. This scoping review seeks to identify, synthesize and map the current evidence on the associations between accessible housing, home modifications, and frailty in community-dwelling older adults aged 65 and above. The aim is to enhance understanding of these relationships, highlight evidence gaps, and support the development of suitable interventions. Methods and analysis This scoping review will follow the framework developed by Arksey and O’Malley and will adhere to the guidelines provided by the Joanna Briggs Institute (JBI) and the PRISMA-ScR checklist. A systematic search will be conducted in PubMed, Embase, the Cochrane Library, Google Scholar, and CINAHL. Rayyan will facilitate deduplication and screening. Titles, abstracts, and full texts will be independently assessed by two reviewers against eligibility criteria. A structured data extraction form will be used to collect information on the study type, publication year, research design, sample characteristics, housing accessibility indicators, methods of frailty assessment, types of home modifications, and key findings. Dissemination Findings will be disseminated in a peer-reviewed journal and presented at conferences.